Abordagens morfológicas e moleculares para delimitação de espécie e investigações de hibridação de duas espécies de Cichla - Mourão, Andrea A. F. [UNESP]; Freitas-Souza, Diogo [UNESP]; Hashimoto, Diogo T. [UNESP]; Ferreira, Daniela C.; do Prado, Fernanda D. [UNESP]; Silveira, Rosicleire V. [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (FapUNIFESP (SciELO), 2017)
The hybridization is a widely-discussed issue in several studies with fish species. For some authors, hybridization may be related with diversification and speciation of several groups, or also with the extinction of populations or species. Difficulties to differentiate species and hybrids may be a problem to correctly apply a management of wild species, because hybrid lineages, especially the advanced ones, may resemble the parental species. The genus Cichla Bloch & Schneider, 1801 constitutes an interesting experimental model, considering that hybridization and taxonomic uncertainties hinder a correct identification. Considering these problems, in this study, we developed genetic methodologies and applied meristic and morphometric approaches in wild samples in order to identify species and for test a possible hybridization between Cichla kelberi Kullander & Ferreira, 2006 and Cichla piquiti Kullander & Ferreira, 2006. For this, C. kelberi, C. piquiti and potential hybrid (carijó) individuals were collected in Paraná and Tietê rivers (SP, Brazil). For meristic and morphometric methods, the individuals were analyzed using the statistical software Pcord 5:31, while for molecular methods, primers for PCR-multiplex were designed and enzyme for PCR-RFLP were selected, under the species-specific nucleotide. All results indicated that the carijó is not an interspecific hybrid, because it presented identical genetic pattern and morphology closed to C. piquiti. Thus, we propose that carijó is a C. piquiti morphotype. In addition, this study promotes a new molecular tool that could be used in future research, monitoring and management programs of the genus Cichla.
Molecular and morphological approaches for species delimitation and hybridization investigations of two Cichla species
Keywords: Carijó; Cichla kelberi; Cichla piquiti; Cluster Similarity; PCA; PCR-multiplex